The effect of different bioceramic root canal sealer removal protocols on the bond strength of composite to coronal dentin in diabetic and non-diabetic patients: an ex vivo study - Arzu Şahin Mantı; Cemile Kedici Alp (BMC Oral Health)
Abstract Background Diabetes mellitus can alter the physical and mechanical properties of dentin, compromising bonding. Furthermore, residual sealer on dentin may inhibit the bond strength. The aim of this study was to evaluate and compare the effects of different cleaning protocols on the adhesive bond strength of composite to coronal dentin contaminated with a tricalcium silicate (TCS)based root canal sealer in diabetic and non-diabetic patients. Methods Diabetic (n = 50) and non-diabetic (n = 50) teeth were randomly divided into two groups. Coronal dentin surface specimens were obtained. The samples were contaminated with a TCS based sealer and then divided into five subgroups, four different cleaning procedures (dry cotton, wet cotton, ultrasonic-15, ultrasonic-30) and a control group (n = 10). The samples were restored with composite. A standard shear bond strength (SBS) test was performed. All failures were categorized as adhesive, cohesive or mixed. Data were analyzed using Independent Samples t-test and One-Way Analysis of Variance at a significance level of p < 0.05. Results SBS values ​​were lower in diabetic dentin group than in non-diabetic dentin group. Dry cotton showed the lowest SBS value in both main groups. Ultrasonic-15 and ultrasonic-30 groups showed equal SBS values ​​in the non-diabetic group (p = 0.001), while the highest SBS was seen in the ultrasonic-30 subgroup in the diabetic dentin group. The highest adhesive failure was observed in the diabetic dentin group, and the dominant failure type was mixed for both groups. Conclusion The use of dry cotton was an insufficient method for removing bioceramic root canal sealer residues from coronal dentin in both the diabetic and non-diabetic patients. 15 s of ultrasonic activation was effective for removing bioceramic root canal sealer remnants from the non-diabetic coronal dentin. However, for the coronal dentin in the diabetic group, 30-sec ultrasonic activation was the most effective method for removing bioceramic root canal sealer remnants.